Development, construct validation and measurement invariance of the Greek cyber-bullying/victimization experiences questionnaire (CBVEQ-G). (December 2016) - Antoniadou, Nafsika; Kokkinos, Constantinos M.; Markos, Angelos
Abstract: This study investigated the construct validity of a newly developed Greek questionnaire assessing cyber-bullying (CB) and cyber-victimization (CV), the Cyber-Bullying and Victimization Experiences Questionnaire-Greek (CBVEQ-G), constructed due to dearth of relevant measures. Analyses were performed on data collected from 1097 Greek adolescents. The structure of the CBVEQ-G was modeled by means of confirmatory factor analysis, and its convergent validity was tested against theoretically related measures. Results supported the validity and reliability of a correlated two-factor (CB, CV) model, while the correlated four-factor model was marginally supported. Measurement invariance across gender and grade level was established, while significantly positive correlations were found between cyber and traditional bullying/victimization, and between CB and antisocial personality traits. Highlights: A correlated two-factor (cyber-bullying and cyber-victimization) model was supported. Measurement invariance across gender and grade level was established. Cyber and traditional bullying/victimization were positively correlated. Cyber-bullying and antisocial personality traits were positively correlated.